The Students’ Styles and Strategies in Learning Relationship to Their Speaking Skills - Adistya, Irine; Marbun, Rismaya; Bunau, Eusabinus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstract: This research discusses two major concerns. First, to find out students’ learning style in learning to improve speaking skills, they are visual, auditory and kinesthetic. Second, to find out strategies used by students who have visual, auditory and kinesthetic learning styles in improving their speaking English skills. The method used in this research was Qualitative Research in the form of Case Study. The tools used in this research were questionnaire and interview. The result showed that the visual learner was 1 student (20 %), auditory learners were 3 students (60 %) and kinesthetic learner was 1 student (20%). As a result, auditory learners were more dominant than kinesthetic and visual learners. Based on the interview conducted to the participants which were 1 visual learner, 3 auditory learners, and 1 kinesthetic learner it was found that visual learner often do not remember information given orally without being able to see it. They memorize using visual clues. Auditory learners need to remember most easily if saying something repeatedly. Auditory learners were able to say something without paying close attention to the person. Kinesthetic learners learn best by moving their bodies, activating their large or small muscles as they learn. They are learners who actually concentrate better and learn more easily when body movement is involved. Keywords: Learning Style, Learning Strategies, English Speaking Skills Abstrak: Penelitianinimembahasmengenaiduahal. Pertama, untukmenentukangayapembelajaransiswadalammeningkatkankemampuanberbicara, yaitu visual, audio, dankinestetik. Kedua, yaituuntukmenentukanstrategi yang digunakansiswa yang memilikigaya visual, audio dankinestetikdalammeningkatkankemampuanberbicarabahasaInggris. Metode yang digunakanadalahKualitatifdalamStudiKasus.Alatpengumpulan data yang digunakanadalahkuesionerdan interview.Hasilmenunjukkanada 1 pelajar visual (20%), 3 pelajar audio (60%) dan 1 pelajarkinestetik (20%).Kesimpulannyapelajar audio lebihdominandibandingkandenganpelajarkinestetikdan visual.Dari interview yang dilakukankepadasiswaditemukanbahwapelajar visual cenderungtidakdapatmengingatdenganbaiktanpamelihatnya.Merekamenghafalmenggunakanpetunjuk visual.Pelajar audio perluuntukmengingathal-haljikamerekamengulangsendiri.Merekadapatmengatakansesuatutanpamemperhatikandenganseksama.Pelajarkinestetikdapatbelajardenganbaikjikamenggunakangeraktubuh.Merekadapatbelajardanmengingatsesuatudenganbaikdimanagerakfisikaldilibatkan. Kata Kunci: Gaya Pembelajaran, StrategiPembelajaran, KemampuanBerbicaraBahasaInggris